Linguagem escrita como prática discursiva: Implicações para o fazer docente em uma Instituição de Educação Infantil no município de São Luís/MA - DOURADO, Inara Sydia dos Santos (2023)
The research titled “WRITTEN LANGUAGE AS DISCURSIVE PRACTICE: Implications for teaching in an Early Childhood Education Institution of São Luís/MA municipality” conducted in the Professional Master’s Degree (PPGEEB-UFMA) develops around the following research question: Which theoretical-methodological assumptions of discursive perspective can subsidize the organization of teaching work, regarding the appropriation of the written language by children of the Early Childhood Education in a municipal public institution of São Luís-MA? Based on this problematization, this study has as its objective to understand the written language appropriation process of children in Early Childhood Education from the assumptions of discursive perspective of language, in the context of a municipal public institution of São Luís-MA in order to elaborate a Notebook with recommendations and strategies to subsidize the organization of the teaching work at this stage of basic education. The objectives presented direct to a qualitative research approach based on the assumptions of the collaborative research type. The research was conducted at UEB Jornalista Batista Matos, having as collaborators two preschool teachers. The semistructured interview, questionnaire and reflective sessions contributed significantly to data generation. The interactions occurred through digital tools and applications such as Google Forms, Whatsapp and Google Meet. The data analysis was carried out in a reflective way by means of the organization of the big theoretical and empirical categories of study: the conceptions of child, development and learning, early childhood education and the conception of language. The data revealed in the course of the investigation presented indications of an educational practice that, although still safe, transits to the discursive field. This research evidenced the need of theoretical sustentation on writing as a discursive and interactive language as well as the need of study about the conceptions of child, early childhood education, development, learning and writing, enabling the performance of a reflective formative process. The research was finalised with the materialisation of the educational product: Caderno dos Porquês: a didactic-methodological investigative instrument in a discursive perspective for the appropriation of the written language of Early Childhood Education children, containing recommendations and strategies in order to subsidize and/or inspire the teachers in work organization with the written language in Early Childhood Education, ensuring the verbal interaction and the comprehension of the true meaning of the acts of reading and writing. The educational product was validated by one of the collaborating teachers, who attested to its applicability potential. The product was validated by one of the collaborating teachers, who attested to its applicability potential. Therefore, it is concluded that through the conduction of a collaborative research, the teacher was mobilised to think of other ways to organize the children’s experience with written culture and to perceive the importance of children’s utterances for the implementation of these practices.